The Effect Of Target Game Training On Shooting Skills In Football Players At SMP Negeri 21 Bengkulu Selatan - Oky Meizal; Deffri Anggara; Megi Personi (Multidisciplinary Journals, 2026)
This study aimed to determine the effect of target games training on shooting skills of soccer players at SMP Negeri 21 Bengkulu Selatan. The research used an experimental method with a total sampling technique, involving 13 players as the sample. Data were collected through pre-test and post-test shooting skills tests over 16 training sessions. The results showed that the pre-test average score was 9.85 (SD = 1.34), while the post-test average score increased to 11.85 (SD = 1.86). Statistical analysis using paired sample t-test revealed tcount = 4.545 > ttable = 1.782 (α = 0.05), indicating a significant effect of target games training on improving shooting skills. These findings suggest that target games can be an effective method to enhance shooting accuracy and performance in junior soccer players.